1996
DOI: 10.1083/jcb.133.3.657
|View full text |Cite
|
Sign up to set email alerts
|

Heterophilic interactions of DM-GRASP: GRASP-NgCAM interactions involved in neurite extension.

Abstract: Abstract. DM-GRASP is an immunoglobulin superfamily cell adhesion molecule that is expressed in both the developing nervous and immune system. Specific populations of neurons respond to DM-GRASP by extending neurites. Neurite extension on DM-GRASP substrates appears to require homophilic interactions between DM-GRASP molecules. We were interested in determining whether DM-GRASP interacts heterophilically with other ligands as well. We have found that eleven proteins from embryonic chick brain membranes consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 47 publications
1
67
0
Order By: Relevance
“…E587 Ag is a member of the L1 family of cell adhesion molecules (Giordano et al, 1997) and therefore may interact with other Ig CAMs. The chick homolog of L1, G4/NgCAM , is able to bind axonin-1 (Kuhn et al, 1991), F11 (Brü mmendorf et al, 1993, and DM-GRASP (DeBernado and Chang, 1996), the fish homolog of which is neurolin (Laessing et al, 1994). The functional relevance of these interactions has been determined in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…E587 Ag is a member of the L1 family of cell adhesion molecules (Giordano et al, 1997) and therefore may interact with other Ig CAMs. The chick homolog of L1, G4/NgCAM , is able to bind axonin-1 (Kuhn et al, 1991), F11 (Brü mmendorf et al, 1993, and DM-GRASP (DeBernado and Chang, 1996), the fish homolog of which is neurolin (Laessing et al, 1994). The functional relevance of these interactions has been determined in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…However, coreceptors have been implicated in L1-mediated outgrowth previously. The FGF receptor (Williams et al, 1994), TAG-1/axonin-1 (Buchstaller et al, 1996), neuropilin-1 (Castellani et al, 2000), and activated leukocyte cell adhesion molecule (DeBernardo and Chang, 1996) have been suggested to be L1 coreceptors. The fact that L1-1147 has good single neurite outgrowth but significantly reduced branching number suggests that the coreceptor can support single neurite outgrowth but does not participate in the initiation of branching.…”
Section: A Coreceptor Is Implicated In L1-mediated Neurite Outgrowthmentioning
confidence: 99%
“…The homophilic properties of SC1 have been revealed using cellular adhesion experiments on substrates and self-aggregation assays in vitro (8,(11)(12)(13). By contrast, previous studies have also reported heterophilic interactions of SC1, such as that with neuron-glia (Ng)-CAM during the extension of neurites from sympathetic neurons as well as that with CD6 in the hematopoietic system (14,15). SC1 homologs have been confirmed in zebrafish, mice, rats and humans (16).…”
Section: Introductionmentioning
confidence: 98%